MOTIVASI KERJA APARAT PEMERINTAH DESA BUNTUNA KECAMATAN BAOLAN KABUPATEN TOLITOLI - Ayu Lestari (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the level of work motivation of the Village Government Apparatus and to determine what factors influence the work motivation of the Village Government Apparatus. This research was conducted in Buntuna Village, Baolan District, Tolitoli Regency. This study uses a descriptive research method with a qualitative approach using the motivation theory of Herzberg Dalam Hasibuan (2006: 186) with indicators as measuring tools that become the contents of the results of observations, interviews, and documentation, which include conditions of the work environment, salaries and benefits, policies organization, relationships with colleagues, job security, quality of supervision. The results of the study prove that the hygine (extrinsic) factor in increasing the work motivation of village officials is not optimal, this can be seen from the Conditions of the Work Environment, Salaries and Benefits, Organizational Policies, relationships with colleagues, job security, quality of supervision. even though the organization's policy in determining the arrival time for office hours is still often late, the village officials are ready to serve the community outside working hours (nights). And the motivator (intrinsic) factor in increasing the work motivation of village officials is optimal, this can be seen from . the work itself, responsibilities, achievements, recognition, and opportunities for advancement.